Prevalence of oral cancer and association of risk factors with treatment outcome status of oral squamous cell carcinoma in Kelantan: a retrospective study - Ahmad, Paras (2020)
Cancer is an unchecked growth of cells due to an imbalance between apoptosis and cell division. Oral cancer is one of the most prevalent cancers worldwide and according to the World Health Organization in 2018, 199,560 out of 665,093 newly diagnosed oral cancer patients died. Oral cancer results from mutations in the DNA that can affect different genes and has multifactorial etiology, most significantly tobacco smoking, alcohol intake, betel quid chewing, genetic predisposition and HPV infection. Oral squamous cell carcinoma (OSCC) represents 90% of the total oral cancers. Tongue is considered as the most commonly involved intra-oral site for oral cancers. Males and old individuals (> 55 years) are more likely to be encountered with oral cancers. In Malaysia, 327 out of 667 newly diagnosed oral cancer patients died in 2018. Radiation and surgery are the only reliable methods of treatment for early and locally advanced carcinoma of the mouth. Chemotherapy alone is not a remedial therapy; however, it may improve results if used in combination with radiation for locally advanced diseases. In this retrospective study (2000 – 2018), data regarding socio-demographic, clinico-pathological factors and treatment outcome associated with oral cancer was gathered from the archives of medical records of Hospital Universiti Sains Malaysia. Out of 301 oral cancer patients, the majority of the patients had OSCC (n=211). The mean age was 55 years. Male patients (n=189, 62.79%) were more than female patients (n=112, 37.21%). Majority of them were non-smoker (n=173, 57.47%), non-alcohol consumer (n=251, 83.38%) and non-betel quid chewer (n=291, 96.67%) Malay (n=207, 68.77%). The most commonly involved site by oral cancer was tongue (n=107). 86.71% patients received treatment and 208 out of 301 patients survived, whereas 93 oral cancer patients died. Alcohol consumption, late presentation/diagnosis, poorly differentiated histological grading and untreated cases were associated with an increased risk of mortality. Other factors including age, ethnicity, betel quid chewing, past family history of tumor, HPV predisposing factors and tumor site had a non-significant association with the mortality rate of OSCC. In conclusion, potential risk factors associated with oral cancer do exist in Kelantanese population.